Incidence of type 2 diabetes and metabolic syndrome by Occupation – 10-Year follow-up of the Gutenberg Health Study - Juliane Bauer; Janice Hegewald; Karin Rossnagel; Sylvia Jankowiak; Michaela Prigge; Julian Chalabi; Matthias Nübling; Alice Freiberg; Merle Riechmann-Wolf; Pavel Dietz; Philipp S. Wild; Thomas Koeck; et al. (BMC Public Health)
Abstract Background In view of demographic change, rising retirement age, and a growing shortage of skilled workers, it is increasingly important to prevent widespread diseases such as type 2 diabetes or its risk factor metabolic syndrome. Since the workplace is an important setting for preventive measures and little is known about incident cases in the working population, the aim of this study was to identify vulnerable occupational groups for whom these interventions are particularly appropriate. Therefore, we investigated the 10-year incidence of type 2 diabetes and metabolic syndrome across occupational groups in Germany. Methods Employees of the population-based Gutenberg-Health-Study (GHS) were examined at baseline (2007–2012) and 10 years later. We calculated age- and sex-standardised incidence rates and standardised incidence ratios (SIR) with a 95% confidence interval (CI) for occupations, job complexity levels, and supervisory and managerial positions. 5954 persons at risk for type 2 diabetes and 5103 at risk for metabolic syndrome were observed. Results Between baseline and follow-up, 388 cases of type 2 diabetes and 1104 cases of metabolic syndrome occurred, and standardised incidences were 6.9% and 22.6%, respectively. The highest incidence of type 2 diabetes was observed in the occupational group “food production and processing” (20.7%) with a threefold increased incidence (SIR = 3.0, 95% CI 1.8–4.7) compared to the total working population of the GHS. Employees in “metal production, processing and construction” had the highest incidence of metabolic syndrome and a two times higher SIR (48.5%; SIR = 2.1, 95% CI 1.4–2.9). There was also a high incidence of both type 2 diabetes and metabolic syndrome in “cleaners” (16.5% and 34.8%) and “drivers and mobile plant operators” (14.8% and 41.2%). An increased incidence of type 2 diabetes and metabolic syndrome was observed with decreasing job complexity levels. Conclusions This study shows wide differences in the incidence of type 2 diabetes and metabolic syndrome between occupational groups and highlights the vulnerability of certain occupations. As the workplace is an important platform for interventions, the findings of this study could guide the development of more nuanced and effective workplace health initiatives to promote a healthier workforce for the future.